The Influence Of Fintech Technology In Digital Wallet Services On Gen Z Purchases On FEBI UINSU Students - Gymnasti Febriani; Muhammad Irwan Padli Nasution; Tuti Anggraini (LP2M IAIN Palopo, 2025)
This study aims to determine the effect of perceived convenience, trust, and supporting facilities as services from digital wallets. The research method used in this research is quantitative with multiple linear regression analysis as the analysis tool. The population of this study were economics and Islamic business students of UIN SU in 2024 as many as 1,130 students. The sample in this study was random sampling, namely by taking respondents randomly and producing 92 respondents. While data analysis uses SPSS 20, Classical Assumption Test, Multiple Linear regression and Hypothesis Test to test data statistically. The results of this study indicate that: (1) Significant value for Convenience of 0.780 and Trust of 0.556 this value> 0.05 from these results shows that there is no significant influence between the variables of Convenience and Trust on purchasing actors at UIN SU Students. (2) Significant value for Facilities, amounting to 0.000, this value is smaller than 0.05 from these results shows that there is a significant influence between the Facility variable on purchasing actors on UIN SU students which is supported by the high interest of students to use attractive features such as cashback and discounts offered by digital wallets to meet their transaction needs.